Novel catalytic systems for carbon dioxide activation - Weilhard, Andreas Sebastian (2019)
This work has developed a series of strategies for the efficient hydrogenation of CO2 to different products with applications as chemicals and fuels. The main focus has been on the synthesis of formic acid (FA). Thermodynamic and kinetic barriers imposed in the hydrogenation of CO2 to formic acid have been overcome by utilizing ionic liquids as additives in the reaction. In the first part the beneficial thermodynamic role of ionic liquids acting as a buffer is described. The buffering properties of ionic liquids are afterwards utilized to develop a structure-activity relationship for a range of catalysts including homogeneous and heterogeneous examples. This enables for the development of highly efficient catalysts in the hydrogenation of CO2 to FA. When CO2 is used as feedstock for carbon-based material, the reduction of the oxidation state at the carbon is critical in order to generate a highly diversified product portfolio. Formic acid is, beneath carbon monoxide, the first product with a reduced oxidation state at the carbon atom. Consequently, formic acid represents a perfect starting point for the development of decarbonised chemical value chains. Furthermore, it is both industrially relevant and has potential to be implemented in future technologies including hydrogen storage schemes, thus underlining the importance for the development for new processes for the synthesis of formic acid. However, the catalytic transformation of CO2 with hydrogen is thermodynamically and kinetically challenging. On the one hand, the formation of formic acid is thermodynamically uphill in gas phase and consequently the equilibrium is commonly shifted to the product side by the addition of stoichiometric amounts of bases. The key here is the formation of formate salts and adducts which would inevitably lead to tedious purifications and to the generation of large amounts of waste. Alternatively, the reaction is carried out in liquid phase which results in an acidic reaction media. On the other hand, CO2 is a kinetically inert molecule, thus necessitating highly nucleophilic, basic metal hydride complexes in order to activate CO2. If no bases are employed, the basicity of the active metal hydride complexes leads inevitably to a fast deactivation of the catalysts. This work addresses the thermodynamic challenges by utilizing ionic liquids (ILs) as additives in the reaction. The ILs act as a buffer during the reaction, thus stabilising the pH of the solution at higher values than that expected by the concentration of FA generated, whilst avoiding the formation of formate salts and adducts. Indeed, the additional stabilisation of formic acid falls into the range of an additional H-bond, compared to the pure solvent system. The buffering properties of ILs allowed also for the screening of different catalysts, including heterogeneous RuFe-nanoalloys. These nanoalloys displayed low activity and selectivity towards the formation of formic acid in comparison to the homogeneous counterparts. One major issue is the preferred formation of carbon monoxide under elevated temperatures, prohibiting efficient transformation rates. Consequently, a wide range of Ru complexes with pyridylideneamide ligands were screened for the hydrogenation of CO2 to formic acid. It was found that the rate of reaction can be enhanced by a) an increased electron density at the metal centre and b) by changing the dominant mechanism for the CO2 insertion into the metal hydride bond. The catalyst durability can be increased by increasing the resistance of the active hydride towards protonation. This is achieved by using pyridinium carbenes as coordinating sites. The catalyst stability and activity with pyridylideneamide ligands is in general good, in line with the literature reports. Based on the experience learned from the pyridylideneamide-based catalysts, a guideline for a highly robust, active and stable catalysts was created. The first example synthesised is a Ru-pincer complexes with N-heterocyclic (NHC) side arms as coordinating sides. Here, the NHC groups, mimic the strong electron donation observed with pyridylideneamides, whilst avoiding side reactions such as electrophilic attacks onto the ligand scaffold. This scaffold allows the performance of the catalyst at demanding reaction conditions without a loss in catalytic activity via the formation of heterogeneous nanoparticles. Furthermore, the structural design of the catalyst avoids the poisoning of the catalyst by the reagents, product or lewis acids. Consequently, the here developed catalyst achieved a TON of 833,800 with an initial turnover frequency (TOF) of 22,000 h-1. These results represent the best catalytic performance reported to date by a factor of 50 (TON) and 22 (TOF), compared to the best performing catalysts reported to date under base free conditions.1